How are words with diacritical vowels represented in the mental lexicon? Evidence from Spanish and German. Issue 4 (21st April 2022) - Perea, Manuel; Labusch, Melanie; Marcet, Ana
ABSTRACT: Recent research has shown that the omission of diacritics in words does not affect the initial contact with the lexical entries, as measured by masked priming. In the present study, we directly examined whether diacritics' omission slows down lexical access using a single-presentation semantic categorisation task ("is the word an animal name?"). We did so in a language in which diacritics reflect lexical stress but not vowel quality (Spanish; e.g. ratón [mouse] vs. raton; Experiment 1) and in a language in which diacritics reflect vowel quality but not lexical stress (German; e.g. Kröte vs. Krote; Experiment 2). In Spanish, word response times were similar for words with diacritics that were either present or omitted. In contrast, German words were responded more slowly when the words' diacritics were omitted. Thus, the function of diacritics in each language determines how words with diacritics are represented in the mental lexicon.